Optimization of nonlinear optical properties by substituent position, geometry and symmetry of the molecule: an ab initio study - Davis, D; Sreekumar, K; Sajeev, Y; Pal, S (Journal of Physical Chemistry B, 2005)
Static polarizability and first- and second-order hyperpolarizability tensors are computed at the correlated level for a series of para-nitroaniline derivatives. The importance of including electron correlation effects in the determination of equilibrium structure and the molecular properties is investigated. A qualitative description of the substitution effects, planarity, and symmetric effect of the molecule on the molecular susceptibility is discussed.